Quercetin promotes cutaneous wound healing in mice through Wnt/β-catenin signaling pathway. (23rd May 2022) - Mi, Yuhui; Zhong, Lei; Lu, Saijian; Hu, Po; Pan, Yang; Ma, Xuelin; Yan, Binghui; Wei, Zhenhuan; Yang, Guangming
Abstract: Ethnopharmacological relevance: Oxytropis falcata Bunge is a legume distributed in Northwest China, which is mainly used to treat knife wounds and inflammation. Quercetin is a bioactive flavonoid in O. falcata and becomes a promising healing compound for its angiogenic and anti-inflammatory activities. However, the healing mechanism of quercetin in cutaneous wound remains elusive. Aim of the study: The purpose of this study was to evaluate the healing effect of quercetin on cutaneous wound models in vivo and in vitro, and to reveal the Wnt/β-catenin pathway and Telomerase reverse transcriptase (TERT) involved mechanisms. Materials and methods: The effects of quercetin on the proliferation and migration of 4 kinds of skin cells were determined by CCK-8 and scratch assay. The wound-healing capacity of quercetin was evaluated in cutaneous wound model of C5 7BL /6 mice and the wound healing degree was observed by histological staining. The expressions of inflammatory factors, growth factors and the related proteins were detected via Western blot and RT-qPCR analyses. The molecular docking was adopted to evaluate the binding ability of quercetin and TERT. Results: Quercetin could promote both proliferation and migration of fibroblasts, and enhance cutaneous wound healing capacity in mice. Compared to the control group, the wound healing rates in low (1.5 mg/mL), medium (3.0 mg/mL) and high dose (6.0 mg/mL) quercetin groups reached 94.67%, 97.31% and 98.42%, respectively. Moreover, the dermal structure in quercetin treated mice restored normal and the content of collagen fiber became abundant after administration. The levels of inflammatory factors, including tumor necrosis factor-α, interleukin-1β and interleukin-6 were significantly reduced after quercetin administration. Among which, the level of IL-1β in cutaneous wound was 0.007 times higher than that of the control group when treated with quercetin of high dose (6.0 mg/mL). The improved level of GSH in quercetin treated cutaneous wounds also indicated its higher antioxidant ability. In addition, dose-dependent positive associations were found in the expression levels of vascular endothelial growth factor, fibroblast growth factor and alpha smooth muscle actin in quercetin treated cutaneous wounds. The significantly upregulated protein levels of Wnt and β-catenin further indicated the important role of quercetin in promoting wound healing in mice. According to molecular docking analysis, the formed hydrogen bonds between quercetin and Ala195, Gln308, Asn369 and Lys372 residues of TERT also indicated the indispensable role of TERT in improving wound healing capacity. Conclusion: Quercetin effectively promoted cutaneous wound healing by enhancing the proliferation and migration of fibroblasts, as well as inhibiting inflammation and increasing the expression of growth factors in mice via Wnt/β-catenin signaling pathway and TERT. It provides a basis for a more thorough understanding of mechanism of action of O. falcata Bunge in the treatment of knife wounds and burns. Graphical abstract: Image 1